Development of an automated theranostic platform combining magnetomotive ultrasound and magnetic hyperthermia - Mazón Valadez, Ernesto Edgar (2023)
Theranostic approaches, combining diagnostic and therapeutic modalities, are gaining recognition as an innovative method to enhance the effectiveness of medical treatments. One specific technique in this field is magnetic hyperthermia (MH), which uses high-frequency magnetic fields and magnetic nanoparticles (MNPs) to target and heat cancerous cells. However, real-time tracking of temperature and MNP location during MH therapy in-vivo presents significant challenges. Magnetomotive ultrasound (MMUS) shows potential in locating MNPs; therefore, enhancing the MH process. However, a major challenge is the implementation of automated switching between the magnetic fields required for MMUS and MH using a single excitation coil. This challenge arises from the different frequency requirements, with MH operating within a 100-500 kHz range and MMUS demanding lower frequency magnetic fields (<100 Hz). Therefore, the goal of this research was to develop a theranostic platform capable of simultaneous MH and MMUS operation using a single excitation coil, enabling potential real-time usage. Overcoming this technological challenge involved the utilization of electromagnetic coupling. To generate MMUS images, a pulse generator based on a capacitor-coil discharge circuit was developed and incorporated into the theranostic platform. The integrated system employed an air-core inductor to generate magnetic field pulses up to 258 mT (2.16 kA). The induced displacements exhibited a direct correlation with temperature variation during a MH procedure. Additionally, the developed MH system achieved temperature rise of 8 °C when employing a magnetic field of 15 kA/m to heat volumes larger than 1 cm3 , indicating its potential for effective MH therapy. The results obtained during this investigation are important for understanding the optimal configurations of the theranostic platform and will guide future in vivo and in vitro studies.